1992
DOI: 10.1159/000236330
|View full text |Cite
|
Sign up to set email alerts
|

Selective IgA Deficiency and Autoimmunity

Abstract: Selective IgA deficiency is the most common primary immunodeficiency. Selective IgA deficiency, as most other immunodeficiencies, is frequently associated with autoimmune phenomena. In this article the authors critically review the literature concerning this association, and discuss the possible mechanisms leading to the increased frequency of autoimmune disorders in subjects with selective IgA deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 61 publications
2
61
0
8
Order By: Relevance
“…The prevalence of autoimmunity in IgAD individuals has been shown to be highly variable, ranging from 7% to 36% in symptomatic IgAD individuals (27), whereas the prevalence of autoimmune disorders in the general population is estimated to be between 3% and 5% (8,9). Recently, Jacob et al reported the frequency of autoimmunity as 19% in their sIgAD patients, which is similar to our results (28).…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of autoimmunity in IgAD individuals has been shown to be highly variable, ranging from 7% to 36% in symptomatic IgAD individuals (27), whereas the prevalence of autoimmune disorders in the general population is estimated to be between 3% and 5% (8,9). Recently, Jacob et al reported the frequency of autoimmunity as 19% in their sIgAD patients, which is similar to our results (28).…”
Section: Discussionsupporting
confidence: 90%
“…104 There is also a clear link between SIgAD and celiac disease. The prevalence of SIgAD in patients with celiac disease is 2.6%, which represents a 10-to 16-fold increase over that in the general population.…”
Section: Org Frommentioning
confidence: 99%
“…A característi ca não-infl amatória da ligação antí genosIgA é fundamental para a manutenção da integridade das mucosas, especialmente no trato gastrointesti nal, onde o indivíduo é exposto a uma grande variedade de antí genos provenientes dos alimentos 2 . Esta característi ca pode ser confi rmada em indivíduos que apresentam lesões infl amatórias gastrointesti nais devido ao aumento das células produtoras de IgG no intesti no, provavelmente causadas pelas enzimas lisossômicas secretadas pelas células polimorfonucleares que se ligam ao complexo antí geno-IgG 28 . Inibição da adesão bacteriana: Um pré-requisito para a patogênese de várias infecções bacterianas é a habilidade do microorganismo em aderir à superfí cie mucosa do hospedeiro.…”
Section: Funções Da Sigaunclassified